2010
DOI: 10.1007/s11999-009-0950-3
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of a Low-stiffness Extensively Porous-coated Femoral Stem at 10 Years

Abstract: Level I, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…While the data of 5 years follow‐up suggest that this fully porous‐coated implant design provides fixation and better maintained peri‐prosthetic cortical thickness and density than conventional implants, a recent study has demonstrated a 10–20% loss in peri‐prosthetic bone at 7 years. This is very similar to that seen with a conventional stem . The authors concluded that that the merit of the Epoch stem in preserving bone mineral is only transient in nature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While the data of 5 years follow‐up suggest that this fully porous‐coated implant design provides fixation and better maintained peri‐prosthetic cortical thickness and density than conventional implants, a recent study has demonstrated a 10–20% loss in peri‐prosthetic bone at 7 years. This is very similar to that seen with a conventional stem . The authors concluded that that the merit of the Epoch stem in preserving bone mineral is only transient in nature.…”
Section: Discussionmentioning
confidence: 97%
“…Another composite implant is the EPOCH hip stem, which has a forged cobalt‐chromium‐molybdenum core section with an outer layer of pure titanium fiber metal mesh applied over a polyaryletherketone (PAEK) middle section . While the data of 5 years follow‐up suggest that this fully porous‐coated implant design provides fixation and better maintained peri‐prosthetic cortical thickness and density than conventional implants, a recent study has demonstrated a 10–20% loss in peri‐prosthetic bone at 7 years. This is very similar to that seen with a conventional stem .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional cementless femoral stems are known to provide a high rate of satisfactory clinical and radiographic performance at long-term followups [1,7,12,14,15,18,33]. However, they may have potential clinical consequences related to stress shielding, thigh pain, periprosthetic fractures, proximodistal dimensional mismatch, and removal during revision [9, 11, 16, 17, 19, 21-23, 35, 38].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, there has been a great deal of interest in conventional cementless and ultrashort stems. Conventional cementless femoral stems demonstrated a good rate of clinical and radiographic performance at long-term follow-up [1][2][3] . Kim et al, in a level I study, compared the use of ultrashort and conventional cementless femoral stems in patients younger than 55, with a mean follow-up of 11.8 years, resulting in absence of significant differences of outcome scores 1 .…”
Section: Total Hip Replacement: New Evidencementioning
confidence: 99%